Analisis Makna Al-Hikmah Dalam Al-Qur’an Surah An-Nahl [16]: 125 : Aplikasi Semiotika Roland Barthes - Syaiful Aslam (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2026)
This study examines the meaning of al-hikmah in the Qur'an Surah An-Nahl [16]: 125 using Roland Barthes' semiotic approach. Al-hikmah is one of the important da'wah methods in Islam, especially to convey messages to scholars and the highly educated public. The purpose of this research is to explore the layers of the meaning of al-hikmah through the analysis of denotations, connotations, and myths according to Barthes' semiotic theory. The research method used is qualitative with a library research approach, collecting data from various literature of interpretation and Arabic dictionaries. The results of the study show that at the denotation stage, al-hikmah means wisdom. At the connotation stage, al-hikmah is interpreted as the ability of the preacher to invite to the way of Allah with true knowledge, conveyed meekly without violence and coercion. Meanwhile, at the mythical stage, al-hikmah reflects moral values and communication ethics that strengthen tolerance and mutual respect in society. This research contributes to understanding the importance of a wise approach in contemporary da'wah.